Cognitive Framework Underlying Learning Strategies for Academic Speaking - Lulus Irawati (English Teaching Journal : A Journal of English Literature, Language and Education, 2013)
This article aims to discuss about cognitive framework underlying learning strategies for acadeic speaking. Cognitive framework underlies learning strategies, since there are four stages of encoding process that cover not only the way store things to be learnt but also the way people organize way store things to be learnt but also the way people organize. Moreover, the learning strategies are helpful for motivating the students  to  be  active  and  creative  in  order  to  develop  their  communicative competence. In the learning strategies, the students are encouraged to participate actively in real communication. Hopefully, this article can give contribution to the teacher and lecturer in teaching speaking skill